Single-Nucleotide Polymorphisms in the 3' Untranslated Region of CORIN Associated With Cardiovascular Diseases in a Chinese Han Population: A Case–Control Study - Zhao, Yichang; Yuan, Xiaoyang; Zhong, Yang; Zhang, Yutao; Zhang, Shushan; Li, Sisi; Zhao, Yuanyuan; Zheng, Wenjun; Liu, Jinqiu; Xia, Yunlong; Yang, Yanzong; Liu, Ying; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Corin is a transmembrane serine protease that activates pro-forms of atrial and brain natriuretic peptides. Numerous studies have indicated that corin played an important role in cardiovascular diseases (CVDs). However, there have been few studies about the correlation between single-nucleotide polymorphisms (SNPs) in the 3' untranslated region (3'UTR) of CORIN and CVDs. The aims of this study were to investigate the associations of three SNPs (rs3749585, rs4695253, and rs12641823) in the 3'UTR of CORIN with CVDs and to find the seed regions of microRNAs (miRNAs) that bind to SNPs of CORIN. Methods and Results: A case–control study (n = 3,537) was performed in a Han population of northeastern China. CVDs included essential hypertension (EH), atrial fibrillation (AF), heart failure (HF), and coronary artery disease (CAD). Genotyping was performed using high-resolution melt analysis. In the EH-control study, rs3749585T was significantly associated with the risk of EH after adjusting for sex and age in allelic (padj = 0.049; OR: 1.113) and dominant (padj = 0.015, OR: 1.233) models. Rs4695253T was significantly associated with the risk of EH in the recessive model after adjusting for sex and age (padj = 0.005, OR: 2.084). Rs3749585T was significantly and negatively associated with AF in the dominant and additive models after adjusting for sex, age, EH, HF, T2DM, and CAD (dominant: padj = 0.009, OR: 0.762; additive: padj = 0.048, OR: 0.873). In the HF-control study and CAD-control study, none of the three SNPs was associated with HF and CAD after adjusting for covariates in any models (padj > 0.05). The levels of high-density lipoprotein (HDL) in rs4695253CC+CT were lower than the levels of HDL in rs4695253TT (42.47 ± 10.30 vs. 48.0 ± 10.24 mg/dl, padj = 0.008). The levels of total cholesterol (TC) in rs4695253CC+CT were lower than the levels of TC in rs4695253TT (164.01 ± 49.15 vs. 180.81 ± 43.92 mg/dl, padj = 0.036). Luciferase assay revealed that the relative luciferase activity of rs3749585CC-transfected cells was significantly decreased by miR-494-3p, in comparison to cells transfected with rs3749585TT (p < 0.001). A significant decrease in the relative luciferase activity of rs3749585TT reporter was observed as compared with rs3749585CC reporter in the presence of miR-1323 or miR-548o-3p (p = 0.017 and 0.012, respectively). Conclusions: We found significant associations between rs3749585T and rs4695253T and EH, between rs4695253T and the levels of TC and HDL, and between rs3749585T and AF. Hsa-miR-494-3p may serve as a potential therapeutic target for EH and AF patients in the future.